Epicurean meteorology : sources, method, scope and organization - Bakker, Fredrik A. (Philosophia Antiqua, 2016)
In Epicurean Meteorology Frederik Bakker discusses the meteorology as laid out by Epicurus (341-270 BCE) and Lucretius (1st century BCE). Although in scope and organization their ideas are clearly rooted in the Peripatetic tradition, their meteorology sets itself apart from this tradition by its systematic use of multiple explanations and its sole reliance on sensory evidence as opposed to mathematics and other axiomatic principles. Through a thorough investigation of the available evidence Bakker offers an updated and qualified account of Epicurean meteorology, arguing against Theophrastus' authorship of the Syriac meteorology , highlighting the originality of Lucretius' treatment of mirabilia , and refuting the oft-repeated claim that the Epicureans held the earth to be flat.